2017
DOI: 10.1002/ijc.30827
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in colorectal cancer survival: A meta‐analysis

Abstract: A meta-analysis was conducted to determine the influence of gender on overall survival (OS) and cancer-specific survival (CSS) in colorectal cancer patients. Major databases were searched for clinical trials, which compare survival differences between male and female for colorectal cancer patients. A list of these studies and references, published in English and Chinese from 1960 to 2017, was obtained independently by two reviewers from databases such as PubMed, Medline, ScienceDirect, the China National Knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
81
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(112 citation statements)
references
References 53 publications
18
81
4
1
Order By: Relevance
“…The assayed merged subgroups showed a trend for saturation for more than 10 samples for CRC and about 20 samples for the control group, whereupon the number of proteins in the summarized proteomes was increased insignificantly. Although there are data regarding the gender-specific difference in overall survival and cancer-specific survival for CRC patients [19], unfortunately, this kind of anthropometric stratification would have been almost impossible within the frame of this study because it would have given even smaller sizes of subgroups with no possibility to review and apply any statistical significance. The common part of the proteome shared between all the groups was determined by comparative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The assayed merged subgroups showed a trend for saturation for more than 10 samples for CRC and about 20 samples for the control group, whereupon the number of proteins in the summarized proteomes was increased insignificantly. Although there are data regarding the gender-specific difference in overall survival and cancer-specific survival for CRC patients [19], unfortunately, this kind of anthropometric stratification would have been almost impossible within the frame of this study because it would have given even smaller sizes of subgroups with no possibility to review and apply any statistical significance. The common part of the proteome shared between all the groups was determined by comparative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A sex-related immunogenic variability after surgical stress has been observed in experimental models, and this might influence outcomes after colon surgery. In the long term this can be associated with higher rates of survival, as suggested by a recent meta-analysis which found that women had better cancer-related survival than men (HR = 0.92, 95% CI = 0.89-0.95) [16]. Visceral obesity makes surgery more difficult, but the increased incidence of AL in this group may also be related to the metabolic effect of obesity.…”
Section: Patient-related Factorsmentioning
confidence: 99%
“…Perforation was not significantly higher after stent placement (3.1% vs 4.8%, no stent vs stent, P = 0.48). The median number of nodes isolated from the specimen was 14 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Pathology and Perioperative Outcomementioning
confidence: 99%
“…Regardless of T2D, CRC incidence, prevalence, and mortality are higher among men than women [5, 6]. However, women aged ≥ 55 years are more often diagnosed with proximal (right-sided) CRC [7], which is associated with more aggressive form of neoplasia than distal (left-sided) CRC [8].…”
Section: Introductionmentioning
confidence: 99%